Influenza vaccination hesitancy in large urban centers in South America. Qualitative analysis of confidence, complacency and convenience across risk groups. - Miguel Ángel González-Block (Public Library of Science (PLoS), 2021)
Influenza vaccination coverage in countries of Latin America is low among priority risk groups, ranging from 5 to 75% among older people. This paper aims to describe and analyze the determinants of influenza vaccination hesitancy through the lens of the 3C model of confidence, complacency and convenience among middle-class, urban risk group populations in Brazil, Chile, Paraguay, Peru, Uruguay, countries in South America with contrasting vaccination coverage. Focus groups were conducted among four risk groups: pregnant women, mothers of children aged <6 years, adults with risk factors, and adults aged ≥60 years in samples of urban residents. Adults with risk factors expressed the most detailed perceptions about confidence in the vaccine. A wide range of perceptions regarding complacency were expressed across risk groups and countries, with pregnant women and mothers showing greater concerns while convenience had a narrower and generally more positive range of perceptions. Participants from Chile and Paraguay expressed the most contrasts regarding confidence and complacency. Information and communication strategies need to be tailored for risk groups while confidence and complacency should be addressed in synergy.